Una medición multidimensional de las actitudes de los docentes y estudiantes del posgrado de rehabilitación oral respecto al uso de adhesivos para prótesis totales - Ortiz Varela, Paulina Alexandra (2020)
Objective: To determine through the use of an instrument, the attitudes that the students and teachers of the Postgraduate course in Oral Rehabilitation have, regarding the use of adhesives for total prostheses. Materials and methods: by applying a validated online questionnaire, it is intended to measure the attitudes on the use of adhesives for dental prostheses, students of the III, IV and V Cohort and teachers of the Medical Specialty in Oral Rehabilitation. Survey of 24 questions, divided into 6 approaches: 1) Perception of denture adhesives. 2) Contribution of adhesives for the development of certain conditions. 3) Use and misuse. 4) Patient education on its use. 5) Inclusion in study plan. 6) Opinion on its use at the clinical level. Thus, after carrying out the statistical procedure, the establishment of an index with two dimensions, ATTITUDE and KNOWLEDGE, was determined. Results: Attitude Index. - In this way it is found that there is a significant correlation between the following dimensions of attitude: dimension 3, dimension 4, dimension 5 and dimension 6, which represent the contribution, usefulness, education, inclusion in the curriculum and opinion of teachers and students respectively. This with a significance level p value equal 0.000 lower than 0.05. Knowledge Index. - The knowledge index depends on opinion, utility, inclusion, education and potential, in that order of importance. Meanwhile, the contribution significantly defines the knowledge index with a value close to unity. Conclusions: In accordance with the scientific evidence, the participants agree that the use of adhesives for total prostheses is beneficial both to improve retention, stability and masticatory efficiency, as well as to include them within the protocols for making total prostheses, in addition to importance of including the subject in the corresponding chair in order to the graduate students to be competent about its use.